Teori Organisasi Struktur Modern Dan Pemikiran Islam Dalam Manajemen Pendidikan Islam - Nabilah Amaliyah Iqbal; Nur Arfiyah Febriani (Prodi Manajemen Dakwah STAIN Mandailing Natal, 2025)
This paper analyzes the integration between modern organizational structure theories and classical Islamic thought in order to develop a more effective, adaptive, and value-based model of Islamic educational management. This study employs a qualitative method through literature review, including content analysis of modern organizational theories such as Weber’s bureaucracy, Fayol’s administrative management, Taylor’s scientific management, systems theory, and network theory, which are then compared with the ideas of Al-Mawardi, Al-Farabi, Ibn Khaldun, and Al-Ghazali. The results show that modern organizational theories provide a strong technical foundation through clear hierarchical structures, rational division of labor, systematic coordination, feedback mechanisms, and collaborative network patterns that enhance the efficiency and effectiveness of educational institutions. However, this technical framework is insufficient without moral-spiritual dimensions. Classical Islamic thought complements modern structures with values of justice, trustworthiness (amanah), consultation (syura), leadership integrity, social solidarity (‘ashabiyyah), and an orientation toward public welfare (maslahah), which reinforce the legitimacy, ethics, and balance of organizational systems. The integration of these two perspectives produces a holistic and character-based model of Islamic educational management by combining structural professionalism with ethical and spiritual values. Thus, the synthesis of modern theories and Islamic thought becomes a strategic foundation for realizing Islamic educational governance that is excellent, responsive, and sustainable.